Unrivalled Influence : Women and Empire in Byzantium - Herrin, Judith (Book collections on Project MUSE., 2013)
Unrivalled Influence explores the exceptional roles that women played in the vibrant cultural and political life of medieval Byzantium. Written by one of the world's foremost historians of the Byzantine millennium, this landmark book evokes the complex and exotic world of Byzantium's women, from empresses and saints to uneducated rural widows. Drawing on a diverse range of sources, Judith Herrin sheds light on the importance of marriage in imperial statecraft, the tense coexistence of empresses in the imperial court, and the critical relationships of mothers and daughters.